Enhancing effects of food components on the production of interferon β from animal cells suppressed by stress hormones - Kabayama, Shigeru (Kluwer Academic Publishers, 1997)
In today's 'modern' society, no one can escape from the stresses of daily life. Stress stimulates the secretion of stress hormones (e.g. cortisol or noradrenaline) which generally suppress the immune response system, thus rendering the body vulnerable to infectious diseases and cancer. Therefore finding anti-stress food components, which diminish and/or inhibit the stress related suppression of the immune response system would be helpful in maintaining and promoting the health of the human population. Here we established a screening system for anti-stress substances using the cultured human cell line MG-63. The production of interferon-β (IFN-β) by MG-63 cells super-induced by Poly (I): Poly (C) was shown to decrease in a dose dependent manner upon the addition of 0.01–10 μg/ml of cortisol or noradrenaline (NA). 1,2–Diacylglycerol (DG) was demonstrated to abrogate this suppression. Lipid from the fermented milk, kefir, also inhibited the influence of cortisol. Kefiran, a polysaccharide secreted from L. kafiranofasiens GKL-28 diminished the cortisol or NA influenced IFN-β production. But phosphatidylcholine had no significant effect in this system. These results suggest that DG, lipids from kefir and kefiran may be equated as anti-stress food component. Abbreviations DG – diacylglycerol; IFN-β – interferon-β; NA – noradrenaline; PC – phosphatidylcholine; Poly (I):Poly (C) – polyinosinic polycytidylic acid.